PENGARUH GOOD GOVERNANCE, PENGENDALIAN INTERNAL DAN SISTEM AKUNTANSI KEUANGAN DAERAH TERHADAP KINERJA PEMERINTAH DAERAH (Studi pada OPD Kota Semarang) - Aisy, Nida Rihadatul; Haryanto, Haryanto (Diponegoro Journal of Accounting, 2024)
This study aims to investigate the impact of Good Governance, Internal Control, and Regional Financial Accounting System on the performance of Local Government in OPD Semarang City, Central Java Province. The population used in the study is the Regional Apparatus Organization (OPD) of Semarang City, and a sample of  94 civil servants of the Semarang City Government was selected using purposive sampling. The data collected was analyzed using multiple regression analysis. The results of the study show that Good Governance and Internal Control have a significant impact on Local Government Performance. However, the Regional Financial Accounting System does not have a significant impact on Local Government Performance.